The female body in K.S. Maniam's play "The Sandpit: Womensis" - Wan Yahya, Wan Roselezam (Universiti Putra Malaysia Press, 2005)
This is a psychoanalytic reading of K.S. Maniam's play "The Sandpit: Womensis" through Laura Mulvey's theory of the male gaze. The findings point to the fact that 'woman' on stage has most often been constructed by men, to be viewed by other men and other women as an object, not a subject. The female character Santha may be seen as taking up the position of the masculine protagonist in expressing her fetishisation of another female character Sumathi as an object of sexual desire. While Santha is represented as older, traditional and asexual, Sumathi's behaviour and appearance are coded as sexually confident and provocative. In this play the female characters enter a discourse in the male subject position and they occupy this constructed space 'docilely'. Thus, the women are able to expose the oppressive representation of the female body as ideological, but are unable to affirm a more adequate one. As a consequence the women are still constructed by male hegemony, lacking a speaking voice. This psychoanalytic reading provides us with a sophisticated understanding of women's present cultural condition. However, it also seems to confine women forever to the status of one who is seen, spoken about, and analysed.